Pengaruh Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) Dalam Meningkatkan Kinerja Manajemen Rantai Pasok (SCM) Suatu Organisasi / Perusahaan - Delvian Yosuky; Renalbi Renalbi; Tio Sania Rachmi; Felix Felix; Ricky Ricky (Serat Acitya, 2022)
In a manufacturing company, of course, it requires supply chain management procedures that can help facilitate the process of managing its business activities in all aspects. ERP is a flexible system that integrates and manages production activities that can increase the performance of a company. This analysis aims to obtain information relating to this ERP system. In this analysis, the author's team chose one of the manufacturing companies in the city of Batam, namely PT Gunung Mas Internasional which had been established since 2015, which is specifically engaged in spring bed manufacturing. This company also uses an ERP application called netsuite